American Women’s Oppression in Sylvia Plath’s Novel The Bell Jar - BELHADDAD, Hassina (My University, 2017)
V Abstract The aim of this work is to discuss the notion of female oppression in literature by looking to The Bell Jar. In order to discuss this notion we looked to the representation of female oppression in literature and the different cultures represented in the novel during the 1960s. The Bell Jar represents the American cold war history with regards to female gender identity by looking to the madness of the world. It investigates the struggle of women to achieve personalized identities. Feminist and psychoanalytic theories are employed to assess strategies of female identity formation by looking to the psychology of the protagonist of the novel Esther Greenwood. Furthermore through using those theories different models of sexuality and female dissatisfaction are defined as illnesses treatable by psychology. In this context, Esther search for a self with whom she can identify becomes the novel’s main question to follow her mother advice or to accept living in the patriarchal society dominated by the man.
Keywords: délicatereading